Comparative analysis of the impact of pre and post covid-19 on academic achievement of post primary school students in Southeast Nigeria - Meze, Michael Ejike (CV. Strata Persada Academia, 2024)
This study utilized a descriptive survey design to examine the perception of teachers on the impact of COVID-19 on academic achievement among post-primary school students in Southeast Nigeria. Data were collected via a structured online questionnaire targeting teachers, comprising demographic details and thirty Likert-scale statements. The survey, distributed through social media, garnered 124 voluntary responses from July 3rd to July 20th, 2024. Initial data processing was done in Microsoft Excel, followed by detailed analysis in SPSS. Descriptive statistics and normality tests were conducted, and the Kruskal-Wallis and Jonckheere-Terpstra tests were used to compare group medians and test hypotheses. Ethical considerations ensured confidentiality and informed consent. Findings indicate that the shift to remote learning during the pandemic exacerbated existing disparities in access to technology, internet connectivity, and educational resources, particularly in rural areas. Lack of electricity and inadequate teacher training in digital pedagogy further hindered online instruction effectiveness. Students faced significant challenges with online learning platforms, home distractions, and decreased motivation due to isolation from the school environment. Language barriers and limited parental support also contributed to these challenges. However, the pandemic prompted innovations in educational delivery methods, highlighting the need for robust infrastructure and comprehensive training to support remote learning. The study underscores the importance of addressing these disparities and enhancing digital literacy to improve academic outcomes and resilience against future disruptions. Recommendations include continued investment in educational technology and support systems to bridge the gap between pre- and post-pandemic academic environments.